Interactive Elaborative Storytelling: Engaging Children as Storytellers to Foster Vocabulary - Vaahtoranta, Enni; Lenhart, Jan; Suggate, Sebastian; Lenhard, Wolfgang (Frontiers in Psychology, 2019)
Positive effects of shared reading for children’s language development are boosted by including instruction of word meanings and by increasing interactivity. The effects of engaging children as storytellers on vocabulary development have been less well studied. We developed an approach termed Interactive Elaborative Storytelling, which employs both word-learning techniques and children’s storytelling in a shared-reading setting. To systematically investigate potential benefits of children as storytellers, we contrasted this approach to two experimental groups, an Elaborative Storytelling group employing word-learning techniques but no storytelling by children, and a Read-Aloud group, excluding any additional techniques. The study was a 3 x 2 pre-posttest randomized design with 126 preschoolers spanning one week. Measured outcomes were receptive and expressive target vocabulary, story memory, and children’s behavior during story sessions. All three experimental groups made comparable gains on target words from pre- to posttest and there was no difference between groups in story memory. However, in the Elaborative Storytelling group children were the least restless. Findings are discussed in terms of their contribution to optimizing shared reading as a method of fostering language.